How does trust in leader influences organizational commitment? A test of a moderated mediation model - Savita S Rai; Navin Kumar Koodamara (Acta Psychologica)
This study examines the link between trust in leader, employee silence, and affective, normative, and continuance organizational commitment. Additionally, this study analyzes how employee silence mediates the link between trust in leader and organizational commitment. This study also examines how ethical leadership moderates the link between trust in leader and employee silence. A cross-sectional quantitative method was adopted to examine the relationship between the constructs. The respondents were public and private sector bank employees located in Southern India. The result reveals that employee silence significantly influences various dimensions of affective commitment, continuance commitment and normative commitment of the employee. There exists a significant relationship between trust in leader and normative commitment. However, the study had found insignificant relationship between trust in a leader and affective commitment and continuance commitment. Interestingly, the results indicate that employee silence significantly mediates the relationship between trust in the leader and affective commitment as well as continuance commitment. Moreover, ethical leadership significantly moderates the relationship between trust in a leader and employee silence. The findings imply that when ethical leadership is high, trust in the leader helps reduce the employees' silent behavior. It is observed that the organization can address the reason for the existence of various motives for an employee's commitment when they focus on trust in the leader and the employee's silent behavior. Another finding of the study states that organizations must groom immediate supervisors' ethical leadership qualities to enhance the relationship between supervisor and subordinate. The presence of silence behavior among employees' is very challenging, as it is unobservable. It is also crucial to identify its presence as employee silence is detrimental to the organization. This study contributes to a better understanding of the relationship between trust in a leader and employee silence and its consequences in shaping various dimensions of organizational commitment in the context of the banking sector.